Implementation, mechanisms of impact and key contextual factors involved in outcomes of the Modification of Diet, Exercise and Lifestyle (MODEL) randomised controlled trial in Australian adults: protocol for a mixed-method process evaluation. Issue 11 (11th November 2020) - Anokye, Reindolf; Radavelli-Bagatini, Simone; Bondonno, Catherine P; Sim, Marc; Blekkenhorst, Lauren C; Connolly, Emma; Bondonno, Nicola P; Schousboe, John T; Woodman, Richard; Zhu, Kun; Szulc, Pawel; Jackson, Ben; et al.
Abstract : Introduction: The Modification of Diet, Exercise and Lifestyle (MODEL) study aims to examine the impact of providing visualisation and pictorial representation of advanced structural vascular disease (abdominal aortic calcification), on 'healthful' improvements to diet and lifestyle. This paper reports the protocol for the process evaluation for the MODEL study. Methods and analysis: The overall aim of the process evaluation is to understand the processes that took place during participation in the MODEL study trial and which elements were effective or ineffective for influencing 'healthful' behavioural change, and possible ways of improvement to inform wider implementation strategies. A mixed-method approach will be employed with the use of structured questionnaires and semistructured in-depth interviews. All 200 participants enrolled in the trial will undertake the quantitative component of the study and maximum variation sampling will be used to select a subsample for the qualitative component. The sample size for the qualitative component will be determined based on analytical saturation. Interviews will be digitally recorded and transcribed verbatim. Qualitative data will be analysed thematically and reported according to the Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines. Ethics and dissemination: The MODEL study process evaluation has received approval from Edith Cowan University Human Research Ethics Committee (Project Number: 20513 HODGSON). Written informed consent will be obtained from all participants before they are included in the study. The study results will be shared with the individuals and institutions associated with this study as well as academic audiences through peer-reviewed publication and probable presentation at conferences. Trial registration number: ACTRN12618001087246.